2015
DOI: 10.1002/pc.23835
|View full text |Cite
|
Sign up to set email alerts
|

High‐performance thermoplastic elastomers/carbon nanotubes nanocomposites: Mechanical behavior, rheology, and durability

Abstract: Advanced polystyrene-b-polybutadiene-b-polystyrene (SBS) based nanocomposites containing bare carbon nanotubes (CNTs) and CNTs bearing hydroxyl functional groups (CNTs-OH) have been formulated and fully characterized. In particular, the reinforcement effect of CNTs and CNTs-OH on SBS was deeply investigated through mechanical and dynamical thermo-mechanical analysis and the rheological response of SBS-based nanocomposites was investigated and discussed. The mechanical properties of SBS/CNTs and even more of SB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
(43 reference statements)
1
7
0
Order By: Relevance
“…This can be attributed to the better dispersion and more homogeneous distribution of the CNTs due to the higher shear forces applied during melt mixing, which was indicated by the lower values of the agglomerate area ratio and their variations (Figure 10). Similar observations were made by Arrigo et al [55] in composites of SBS and modified MWCNTS containing COOH groups, which were melt mixed in a Brabender mixer at 50 rpm and 100 rpm. The study also reported a significant influence of processing temperature on the mechanical properties, an observation that could not be validated from the results obtained in the context of the present work.…”
Section: Resultssupporting
confidence: 85%
“…This can be attributed to the better dispersion and more homogeneous distribution of the CNTs due to the higher shear forces applied during melt mixing, which was indicated by the lower values of the agglomerate area ratio and their variations (Figure 10). Similar observations were made by Arrigo et al [55] in composites of SBS and modified MWCNTS containing COOH groups, which were melt mixed in a Brabender mixer at 50 rpm and 100 rpm. The study also reported a significant influence of processing temperature on the mechanical properties, an observation that could not be validated from the results obtained in the context of the present work.…”
Section: Resultssupporting
confidence: 85%
“…In this way, the aggregation of filler will promote the formation of the internal stress concentration of composite, therefore, the ability of composites to resist external forces has been reduced. [53][54][55][56] In common, the mechanical properties of rubber-matrix composites depend on the dispersibility of filler and the interaction between filler and rubber-matrix. 53 The dispersibility and wettability of CB-g-CTHBP's in rubber-matrix demonstrate obvious improvement after grafted with hyperbranched polymer, and the interaction has also increased between the fillers and rubber-matrix.…”
Section: Effect Of Cb and Cb-g-cthbp Content On The Rubber-matrix Composites Mechanical Propertiesmentioning
confidence: 99%
“…22 Arrigo et al also observed similar phenomenon. 23 The researchers reported that due to better interaction between the OH-modified CNTs and polystyrene- b -polybutadiene- b -polystyrene (SBS), the nanocomposites prepared using the treated CNT have higher viscosity and improved storage modulus.…”
Section: Rheologymentioning
confidence: 99%